Pelatihan Pemasaran Online Berbasis Digital untuk UMKM di Kecamatan Tanotombangan, Angkola, Kabupaten Tapanuli Selatan - Alwendi, Alwendi; Mandopa, Andi Saputra; Hasibuan, Erwina Azizah (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Online media is a method of presenting and marketing products, for example, through advertising. The explanation in the webinar includes the benefits of online marketing and the activities required. Service Method, a preliminary survey to understand partner needs. Planning online marketing activities. Counseling on the creation and use of online marketing for each branch. Evaluate activities to ensure they are in accordance with planning. Online media now plays a key role in buying, selling, and product introduction. SME Fortuna Handycraft, with 10 years of experience, is faced with technological, marketing, and managerial obstacles. The UKM Indonesia Bangkit program provides a solution by procuring production machines and an Android-based Management Information System (SIMBA). This solution increases productivity and helps in marketing through online communications.